Numerical study of low-velocity impact performance of hybrid carbon/Twaron woven fabric - Canyi Huang; Lin Tang; Xiaofang Zheng; Lina Cui; Yajun Liu (Journal of Engineered Fibers and Fabrics)
In the present study, a finite element impact model of plain-woven fabric was developed and analyzed using commercial FEM code ANSYS ® and then validated via a drop-weight impact experiment. Then numerical analysis was carried out to investigate the low-velocity impact performance of hybrid carbon/Twaron fabric. During the analysis, several factors were considered, such as different hybrid ratios of plain fabric, hybrid fabric with different weaves, and the case of a hybrid multi-layer fabric panel. The results show that among the different types of hybrid plain fabric, the impact scenario of plain fabric with a hybrid ratio of 1:1, where carbon yarns are only in the warp direction and Twaron yarns are only in the weft direction (M4-2), has the best impact resistance performance. The impact scenario M4-2 performed excellently in other weaves, such as twill weave, while impact scenario M4-1 (plain fabric with a hybrid ratio of 1:1, one carbon yarns interval with one Twaron yarn) in basket weave showed high suitability for body armor in terms of impact protection. Additionally, arranging Twaron fabric in the top layers of a hybrid multi-layer carbon/Twaron fabric panel yielded superior impact resistance performance during low-velocity impact events compared to other layer arrangements.